2008
DOI: 10.1097/ogx.0b013e31817d4e8d
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Unexplained Infertility With Aromatase Inhibitors or Clomiphene Citrate

Abstract: Treatment of unexplained infertility is empiric and different regimens or protocols have been used so far. Clomiphene can be used alone or combined with gonadotrophins. Aromatase inhibitors may offer an alternative for first-line treatment. To compare the efficacy of aromatase inhibitors versus climiphene, we conducted a systematic review and meta-analysis for randomized controlled trials comparing the above regimens to estimate live pregnancy rates in women with unexplained infertility. Trials were located th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…The majority of studies comparing clomiphene citrate with letrozole for superovulation in patients with unexplained infertility undergoing IUI revealed that although letrozole induced fewer mature follicles compared with clomiphene citrate the pregnancy rate was comparable between both management options[9,12]. We think that letrozole resulted in comparable pregnancy rate as clomiphene citrate, in spite of less number of mature oocytes induced, because it has no adverse effect on endometrium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies comparing clomiphene citrate with letrozole for superovulation in patients with unexplained infertility undergoing IUI revealed that although letrozole induced fewer mature follicles compared with clomiphene citrate the pregnancy rate was comparable between both management options[9,12]. We think that letrozole resulted in comparable pregnancy rate as clomiphene citrate, in spite of less number of mature oocytes induced, because it has no adverse effect on endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that the combination of exogenous gonadotropins with letrozole increased the number of mature oocytes and therefore improved the outcome of IUI cycles in patients with unexplained infertility [6,12]. However, the addition of exogenous gonadotropins to letrozole increases the cost of IUI cycle and is associated with increased risk of higher order multiple pregnancy and ovarian hyperstimulation syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in diagnostic methods to evaluate the infertile couples and variable means of data collection make them very inhomogeneous. Women suffering from unexplained subfertility have both delayed and decreased fecundity with an average cycle fecundity reported between 2 and 4 % per menstrual cycle [32,33].…”
Section: Epidemiologymentioning
confidence: 99%
“…These include ovulation induction with clomiphene citrate (CC) [8], gonadotrophins (HMG) [9], or aromatase inhibitors [10], flushing the uterine cavity with various physiological solutions or radio-opaque medium [11], empirical use of bromocryptin [12] or danazol [13], intrauterine insemination (IUI) with or without controlled ovarian hyperstimulation (COH) [14][15][16][17][18], intraperitoneal insemination (IPI) [19], fallopian tube sperm perfusion [20], gamete intrafallopian transfer (GIFT), as well as in vitro fertilization (IVF) with or without intracytoplasmic sperm injection (ICSI) [16,[21][22][23]. This chapter will evaluate the role of IVF in unexplained female infertility in the light of evidence.…”
Section: Introductionmentioning
confidence: 99%